2015
DOI: 10.18632/oncotarget.4494
|View full text |Cite
|
Sign up to set email alerts
|

Genomic amplification of 9p24.1 targeting JAK2, PD-L1, and PD-L2 is enriched in high-risk triple negative breast cancer

Abstract: We used DNA content flow cytometry followed by oligonucleotide array based comparative genomic hybridization to survey the genomes of 326 tumors, including 41 untreated surgically resected triple negative breast cancers (TNBC). A high level (log 2 ratio ≥1) 9p24 amplicon was found in TNBC (12/41), glioblastomas (2/44), and colon carcinomas (2/68). The shortest region of overlap for the amplicon targets 9p24.1 and includes the loci for PD-L1, PD-L2, and JAK2 (PDJ amplicon). In contrast this amplicon was absent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
3
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(140 citation statements)
references
References 42 publications
6
128
3
3
Order By: Relevance
“…In addition, others have demonstrated that oncogenic alterations can induce PD-L1 expression. [48][49][50] The correlations we report between lymphocyte infiltration (in particular CD3 and CD8 C ) and distribution (immunotype) with PD-L1 expression, and the lack of any association with BRAF mutational status, suggest that PD-L1 expression by human melanoma cells can be explained predominantly by adaptive resistance. We only found a single case where PD-L1 expression was observed in greater than 5% of the tumor cells in the absence of any CD8 C T cells, a result consistent to Taube and colleagues' finding.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, others have demonstrated that oncogenic alterations can induce PD-L1 expression. [48][49][50] The correlations we report between lymphocyte infiltration (in particular CD3 and CD8 C ) and distribution (immunotype) with PD-L1 expression, and the lack of any association with BRAF mutational status, suggest that PD-L1 expression by human melanoma cells can be explained predominantly by adaptive resistance. We only found a single case where PD-L1 expression was observed in greater than 5% of the tumor cells in the absence of any CD8 C T cells, a result consistent to Taube and colleagues' finding.…”
Section: Discussionmentioning
confidence: 73%
“…For certain subtypes of Hodgkin's lymphoma as well as triple negative breast cancer, gene amplification of the PD-L1 locus (Chr.9 p24.1) has been described. 32,34 Clinical studies with PD-1 inhibitors for these entities are ongoing. 35 In lymphoma, the amplified region may encompass the adjacent genes PD-L2 and JAK2.…”
Section: Pd-l1 Expression (Tumor Cells)mentioning
confidence: 99%
“…The locus of PD-L1 and PD-L2 at human chromosome 9p24 was found to be amplified in 12 of 41 (29%) triplenegative breast carcinomas, but not in any of the 23 ERpositive or Her2-positive carcinomas examined (19). The amplicon, which included also the locus of the JAK2 kinase gene, was confirmed to be translated producing higher levels of mRNA than those observed in non-amplified patients.…”
Section: Ctla-4mentioning
confidence: 81%